Tantalum-silver coating modified bone implant and preparation method thereof
By depositing the tantalum silver coating on the surface of the titanium alloy matrix using magnetron sputtering technology and performing heat treatment, the problem of poor bone integration ability of bone implants is solved, and better biocompatibility and antibacterial properties are achieved.
Patent Information
- Application Number
- CN202411941103.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The bone integration capability of existing bone implants is poor, and traditional coating technology has the problem that the thickness is difficult to evenly control and insufficient binding force with the matrix.
Magneto-controlled sputtering method is used to deposit tantalum and silver on the surface of the titanium alloy substrate in sequence to form a tantalum silver coating, and the coating is heat treated to improve its binding force and biocompatibility with the substrate.
It improves the bone integration ability, biocompatibility and antibacterial properties of bone implants, enhances the binding force between the implant and bone tissue, reduces the risk of infection, and improves the success rate of the surgery and the quality of patients' rehabilitation.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material surface modification, and relates to a tantalum-silver coating modified bone implant and a preparation method thereof. Background Art
[0002] Bone implants, as an important tool in modern medicine, are widely used in repairing jaw defects, installing dental implants, and performing joint replacement surgeries. In order to ensure that the implants can function in the human body for a long time and stably, ideal bone implants need to have a series of key characteristics. First, biocompatibility is the basic requirement for bone implants. This means that the implants must be able to coexist peacefully with human tissues without triggering immune or rejection reactions. Secondly, good mechanical properties are also essential because implants need to withstand various mechanical pressures from the human body. In addition, corrosion resistance is also an important indicator for measuring the quality of bone implants, which determines the durability and stability of implants in the human body. In addition to the above basic characteristics, ideal bone implants should also have good bone integration and antibacterial capabilities. Bone integration refers to the ability of the implant to directly contact the surrounding bones and tissues after implantation into the body to form a bony bond. Under an optical microscope, it can be seen that the new bone tissue is directly attached to the metal surface, and there is no fibrous connective tissue interface layer in between, that is, the implant can form a tight bond with the surrounding bone tissue, thereby ensuring the stability and long-term effect of the implant. Osseointegration is the direct structural and functional connection between bone tissue and the surface of an implant. It is a structural response of living bone tissue to inanimate implants. Osseointegration is a complex dynamic process involving the body's immune response, as well as the adhesion, proliferation and osteogenic differentiation of related pioneer cells. When there is no progressive relative movement between the implant and the bone it is in direct contact with, the implant is considered to have achieved osseointegration. Antibacterial ability helps reduce the risk of implant infection and improve the success rate of surgery.
[0003] Among the current bone implant materials, metal materials occupy a dominant position. Among them, pure titanium and titanium alloys have become the first choice for bone implant materials due to their excellent biocompatibility and mechanical properties. However, despite the many advantages of pure titanium and titanium alloys, their bone integration ability still needs to be improved. Therefore, modifying the surface of pure titanium and titanium alloys to enhance their bone integration ability has become a hot topic in current research. Although traditional coating technology can improve the performance of implants to a certain extent, it has defects such as difficulty in uniformly controlling thickness and insufficient bonding with the substrate. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a tantalum-silver coating modified bone implant and a preparation method thereof, thereby solving the technical problem of poor bone integration ability of the bone implant in the prior art.
[0005] The present invention is achieved through the following technical solutions: A method for preparing a tantalum-silver coating modified bone implant comprises the steps of sequentially depositing tantalum and silver on a base metal surface by magnetron sputtering in an argon atmosphere, and heat treating the magnetron sputtered base material to obtain the tantalum-silver coating modified bone implant.
[0006] Preferably, the purity of the argon gas is greater than 99.999%, and the flow rate of the argon gas is 20-100 sccm.
[0007] Preferably, during the magnetron sputtering process, the target current is 1-3A, and the magnetron sputtering time is 18-450min.
[0008] Preferably, during magnetron sputtering, the vacuum degree is 10 -3 ~10 -5 Pa.
[0009] Preferably, during the magnetron sputtering process, a negative bias voltage is applied between the target and the substrate, and the bias voltage is -100~-200V.
[0010] Preferably, during the magnetron sputtering process, a magnetic field is applied between the target and the substrate, and the magnetic field strength is 200-500G.
[0011] Preferably, the heat treatment is carried out at a temperature of 150-300° C. and for a time of 1-3 hours.
[0012] Preferably, before magnetron sputtering, the substrate is pretreated, wherein the substrate is placed in acetone, alcohol and deionized water for ultrasonic cleaning in sequence, and then vacuum dried at 150-200°C, wherein the vacuum degree is 10 -3 ~ 10 -2 Pa.
[0013] A tantalum-silver coating modified bone implant is prepared by the above method; the bonding force between the tantalum coating and the bone implant is 20-60 MPa, and the roughness is 15-100 nm.
[0014] Preferably, the thickness of the tantalum coating is 200nm~5µm.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention discloses a method for preparing a bone implant modified by a tantalum-silver coating. The tantalum-silver coating is formed by sequentially depositing tantalum and silver on the surface of a titanium alloy substrate. The coating can form an endogenous electric field with a cell membrane, which helps to promote the attachment, proliferation and differentiation of cells on the surface of the implant. In particular, tantalum, as a metal with good biocompatibility, is easy for cells to recognize and bind on its surface, while silver has certain antibacterial properties and can reduce the risk of infection after implantation, thereby jointly improving the bone integration ability. The tantalum-silver coating not only improves the potential difference on the surface of the titanium alloy substrate, but also improves the overall biocompatibility. Tantalum has very good compatibility with human tissues and almost no rejection reaction will be caused. At the same time, the addition of silver can further inhibit bacterial growth, reduce inflammatory reactions around implants, and facilitate postoperative recovery; the formation of an endogenous electric field can guide the directional growth and arrangement of cells on the surface of the implant, thereby optimizing cell behavior. This optimization not only helps to form a denser and firmer bone-implant interface, but also improves the stability and durability of the implant; silver, as a broad-spectrum antibacterial agent, can effectively kill or inhibit the growth of a variety of bacteria. Adding a silver coating to a bone implant can significantly reduce the risk of postoperative infection, improve the success rate of surgery and the quality of patient recovery. Therefore, the tantalum-coated modified bone implant improves the bone integration ability of the implant, enhances biocompatibility, optimizes cell behavior, and improves antibacterial properties.
[0016] Furthermore, the purity of the argon gas is greater than 99.999%, and the flow rate of the argon gas is 20-100 sccm. The argon gas with a purity greater than 99.999% contains almost no impurities, which can ensure that no additional pollutants are introduced during the sputtering process, thereby ensuring the purity and quality of the coating. High-purity argon gas can also provide a stable sputtering environment, reduce the sputtering instability caused by gas impurities, and improve the sputtering efficiency and the uniformity of the coating; the argon gas flow rate is controlled within the range of 20-100 sccm, which can ensure the fluidity and uniformity of the gas in the sputtering area, which is beneficial to the effective sputtering and deposition of target atoms. The appropriate flow rate can also reduce the problem of decreased sputtering efficiency or unstable coating quality caused by excessive or too small gas flow rate; high-purity argon gas can effectively isolate oxygen in the air and reduce the oxidation of the target material and the deposited coating during the sputtering process, which is crucial for the preparation of high-quality tantalum and silver coatings, because oxidation will reduce the conductivity, corrosion resistance and biocompatibility of the coating. Under appropriate argon flow rate, the sputtered target atoms can be more effectively deposited and combined on the substrate surface to form a dense and uniform coating. The dense coating structure helps to improve the mechanical properties and durability of the coating, and is also beneficial to improving the biocompatibility and antibacterial properties of the coating.
[0017] Further, in the magnetron sputtering process, the target current is 1~3A, and the magnetron sputtering time is 18~450min. The size of the target current directly affects the sputtering rate. In the range of 1~3A, the target current is moderate, which can not only ensure a sufficient sputtering rate, but also avoid excessive current causing overheating of the target material, unstable sputtering or reduced coating quality. The appropriate target current also helps to increase the energy of the sputtered atoms, so that they can be more effectively deposited on the substrate surface to form a dense and uniform coating; the sputtering time is within the range of 18~450min, which can ensure that the coating reaches the required thickness and uniformity. Too short sputtering time may cause the coating to be too thin or uneven, and too long sputtering time may increase production costs and energy consumption. During this time period, the sputtering process can be carried out stably, which is conducive to the formation of high-quality coatings; appropriate target current and sputtering time can reduce the introduction of impurities during the sputtering process, thereby improving the purity of the coating. High-purity coatings are conducive to improving the conductivity, corrosion resistance and biocompatibility of the coating; under appropriate sputtering conditions, sputtered atoms can more effectively combine with the substrate surface to form a firm coating. This helps improve the durability and stability of the coating.
[0018] Furthermore, during magnetron sputtering, the vacuum degree is 10 -3 ~10 -5 Pa, within this vacuum range, the probability of interaction between the evaporated material and other gas molecules can be significantly reduced, thereby reducing the possible risk of "contamination", which helps to improve the purity and quality of the film layer and avoid the introduction of unnecessary impurities. Moderate vacuum helps the evaporated material to obtain better scattering properties, allowing it to be more evenly deposited on the substrate surface, which helps to form a smooth and dense film and improve the overall quality of the coating; high vacuum can reduce the scattering of gas molecules on the film and reduce energy loss during the sputtering process, thereby improving sputtering efficiency; too low a vacuum will cause unnecessary reactions between the evaporated material and the residual gas molecules, introducing impurities or causing the film layer structure to become loose, and within this vacuum range, this situation can be avoided, ensuring the stability and reliability of the film layer and improving the bonding strength of the film layer.
[0019] Furthermore, during the magnetron sputtering process, a negative bias voltage of -100~-200V is applied between the target and the substrate. The negative bias voltage can attract positive ions in the plasma to accelerate toward the substrate. When these high-energy ions bombard the surface of the substrate, they transfer energy and promote the rearrangement of atoms on the surface of the substrate, which helps to form a denser and more uniform coating. Appropriate negative bias voltage can reduce defects such as pores and cracks in the coating and improve the overall quality of the coating. Negative bias voltage can also affect the microstructure of the coating and enhance surface roughness. The ion bombardment effect under negative bias voltage can enhance the interaction between the atoms of the coating and the atoms of the substrate and promote chemical bonding between them, thereby improving the bonding force between the coating and the substrate. Strong bonding force helps to reduce the risk of peeling of the coating during use and increase the service life of the coating. Negative bias voltage can increase the energy of the sputtered atoms, making them easier to sputter from the surface of the target and more effectively deposited on the substrate. Under appropriate negative bias voltage, the sputtering rate can be optimized, thereby ensuring the quality of the coating while improving production efficiency.
[0020] Furthermore, during the magnetron sputtering process, a magnetic field is applied between the target material and the substrate, and the magnetic field strength is 200~500G. The magnetic field can bind and extend the movement trajectory of electrons, increase the collision probability of electrons and working gas, and then promote the occurrence of ionization. The electrons generated again after ionization also join the collision process, which can increase the collision probability by several orders of magnitude and effectively utilize the energy of electrons. Therefore, in the abnormal glow discharge that forms high-density plasma, the plasma density increases, and the rate of sputtering target atoms also increases accordingly. The magnetic field can guide the movement trajectory of the sputtered particles, so that they bombard the substrate surface more concentratedly, thereby improving the sputtering efficiency. The magnetic field can constrain the movement of electrons near the target surface, reduce the direct bombardment of electrons on the substrate, thereby reducing the temperature rise of the substrate. At the same time, the magnetic field can make the sputtered particles more evenly distributed on the surface of the substrate, thereby improving the uniformity of the coating; the magnetic field can reduce the scattering phenomenon during the sputtering process, reduce the probability of the formation of defects such as pores and cracks in the coating, thereby improving the overall quality of the coating; the magnetic field can accelerate the bombardment of positive ions on the substrate, increase the bombardment energy and density, thereby promoting the interaction and chemical bonding between the coating atoms and the substrate atoms, and improving the bonding strength between the coating and the substrate; the magnetic field can also affect the interface structure between the coating and the substrate, making it tighter and stronger, further improving the bonding strength between the coating and the substrate.
[0021] Furthermore, the temperature of the heat treatment is 150-300°C and the time is 1-3 hours. The heat treatment helps the metallurgical reaction between the coating and the substrate to form a chemical bond, thereby improving the adhesion of the coating. Appropriate temperature and time can ensure that the metallurgical reaction is fully carried out without causing excessive thermal damage to the coating or the substrate. During the heat treatment process, the atoms in the coating will be rearranged and diffused, which will help eliminate pores and cracks in the coating and improve the uniformity and density of the coating. Through heat treatment, the grains in the coating may be refined and the number of grain boundaries increased, thereby improving the hardness and wear resistance of the coating; heat treatment can release the stress generated by the coating during the sputtering process and reduce the risk of cracking of the coating due to excessive stress; at the same time, heat treatment under this condition also improves the stability and bonding strength of the coating.
[0022] Furthermore, before magnetron sputtering, the substrate is pretreated by placing the substrate in acetone, alcohol and deionized water for ultrasonic cleaning in sequence, and then vacuum drying at 150-200°C, wherein the vacuum degree is 10 -3 ~ 10 -2 Pa can improve the cleanliness of the coating surface.
[0023] Placing the substrate in acetone, alcohol and deionized water for ultrasonic cleaning in turn can effectively remove pollutants such as grease, dust, oxides, etc. on the substrate surface. If these pollutants remain on the substrate surface, they will affect the adhesion and deposition of particles during the sputtering process, thereby reducing the quality and performance of the coating. Ultrasonic cleaning can penetrate into the tiny pores on the surface of the substrate through the oscillation of ultrasonic waves, and completely remove pollutants that are difficult to remove, thereby improving the surface cleanliness of the substrate. A clean substrate surface is conducive to the formation of chemical bonds between the sputtered particles and the substrate, thereby improving the adhesion between the coating and the substrate. In addition, vacuum drying at 150~200℃ can remove residual moisture on the surface and inside of the substrate. If these moisture remain in the substrate, they may cause defects such as bubbles and cracks during the sputtering process, affecting the quality and stability of the coating. During the vacuum drying process, by controlling the vacuum degree at 10 -3 ~ 10 -2Pa range, the air can be isolated to prevent the substrate from oxidation reaction during the drying process, which helps to maintain the original performance and structure of the substrate and provide a good foundation for the subsequent sputtering coating process. The surface of the substrate after vacuum drying is drier and cleaner, which is conducive to the uniform deposition and adhesion of sputtering particles on the substrate. This can improve the quality, uniformity and stability of the coating; the surface of the pretreated substrate is smoother and cleaner, which is conducive to the smooth progress of the sputtering coating process, which can improve the efficiency and quality of the coating. The pretreated substrate can significantly improve the adhesion, hardness and wear resistance between the coating and the substrate, which helps to extend the service life of the coating and improve the reliability and stability of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 This is a microscopic morphology of the material fault layer modified by the tantalum coating prepared in Comparative Example 1 of the present invention; Figure 2 The surface potential difference and surface morphology of the material modified by the tantalum coating prepared in Comparative Example 1 of the present invention; Figure 3 This is a microscopic morphology of the material fault layer modified by the tantalum coating prepared in Comparative Example 2 of the present invention; Figure 4 The surface potential difference and surface morphology of the material modified by the tantalum coating prepared in Comparative Example 2 of the present invention; Figure 5 This is a microscopic morphology of the material fault modified by the tantalum coating obtained in Comparative Example 3 of the present invention; Figure 6 The surface potential difference and surface morphology of the material modified by the tantalum coating prepared in Comparative Example 4 of the present invention; Figure 7 This is a fault microscopic morphology of the material modified by the tantalum-silver coating obtained in Example 1 of the present invention; Figure 8 The surface potential difference and surface morphology of the material modified with the tantalum-silver coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0027] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0028] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0029] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0030] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0031] The invention provides a method for preparing a tantalum-silver coating modified bone implant, comprising the steps of sequentially depositing tantalum and silver on the surface of a base metal by a magnetron sputtering method under an argon atmosphere, and heat-treating the magnetron sputtered base material to obtain the tantalum-coated modified bone implant.
[0032] The purity of the argon gas is greater than 99.999%, and the flow rate of the argon gas is 20-100 sccm.
[0033] During the magnetron sputtering process, the target current is 1-3A, and the magnetron sputtering time is 18-450min.
[0034] During magnetron sputtering, the vacuum degree is 10 -3 ~10 -5 Pa.
[0035] During magnetron sputtering, a negative bias voltage is applied between the target and the substrate, and the bias voltage is -100~-200 V. At the same time, during magnetron sputtering, a magnetic field is applied between the target and the substrate, and the magnetic field strength is 200~500G.
[0036] Preferably, the heat treatment temperature is 150-300° C. and the time is 1-3 hours.
[0037] Before magnetron sputtering, the substrate was pretreated by placing the substrate in acetone, alcohol and deionized water for ultrasonic cleaning, and then vacuum drying at 150-200°C, wherein the vacuum degree was 10 -3 ~ 10 -2 Pa.
[0038] In addition, the present invention also discloses a tantalum-silver coating modified bone implant, which is prepared by the above method; the bonding force between the tantalum coating and the bone implant is 20-60MPa, and the roughness is 15-100nm; the thickness of the tantalum coating is 200nm-5µm.
[0039] By adopting magnetron sputtering technology, the present invention can deposit a coating with controllable thickness, uniformity and stability on a titanium or titanium alloy metal substrate. By changing the order of target metal sputtering, the osteogenic ability and antibacterial ability of the bone implant are effectively improved, and the bone integration ability of the bone implant is further improved. Compared with traditional coating technology, the coating thickness of the present invention is controlled between 200nm and 5µm, which not only ensures the stability and uniformity of the coating, but also avoids the adverse reactions that may be caused by too thick coatings. By comparing the different coating thicknesses and the different sputtering orders of different target metals, the present invention aims to find a composite metal coating with the best bone integration ability. Through a series of verifications, the preferred 500nm thick tantalum coating has the best mechanical properties, and the 500nm thick tantalum coating has the best osteogenic ability. At the same time, tantalum and silver are deposited on the surface of the base metal in sequence, which has the best osteogenic and antibacterial abilities, which provides a more flexible solution for different clinical needs.
[0040] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0041] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0042] Comparative Example 1 The base metal is cut into sheets or columns of appropriate sizes and ultrasonically cleaned in deionized water. Ultrasonic cleaning is performed in acetone, alcohol and deionized water respectively to ensure surface cleanliness. And dried in a vacuum environment at 200°C. Tantalum coating is deposited by magnetron sputtering equipment in an environment with a vacuum degree of 10^-5 Pa. The target current is set to 0.3A, the substrate temperature is maintained at room temperature, and the argon flow rate is constant at 20 sccm. After sputtering coating, appropriate heat treatment (400°C for 1 hour) can be performed to improve the adhesion and uniformity of the coating. The surface morphology of the coating is observed by scanning electron microscopy (SEM), such as Figure 1 , indicating that the coating is uniform and dense.
[0043] Comparative Example 2 The difference between this embodiment and comparative example 1 is that the thickness of the tantalum coating is 500 nm.
[0044] Comparative Example 3 The difference between this embodiment and comparative example 1 is that the thickness of the tantalum coating is 750 nm.
[0045] Example 1 A method for preparing a tantalum-silver coating-modified bone implant comprises shearing a base metal into flakes or columns of suitable size and ultrasonically cleaning them in deionized water. Ultrasonic cleaning is performed in acetone, alcohol and deionized water respectively to ensure surface cleanliness. The surface is dried in a vacuum environment at 200°C. Under a vacuum degree of 10^-5 Pa, tantalum is first sputtered and then silver is sputtered on the surface of the base metal by a magnetron sputtering device. The target current is set to 0.3A, the substrate temperature is maintained at room temperature, and the argon gas flow rate is constant at 20sccm. After sputtering the coating, the coating is kept at 400°C for 1 hour to improve the adhesion and uniformity of the coating.
[0046] The prepared materials are characterized by the microscopic topography of the fault, the surface potential difference of the material and the surface topography. Specifically: Figure 1 This is a microscopic morphology of the material fault modified by the tantalum coating prepared in Comparative Example 1 of the present invention. As can be seen from the figure, the tantalum coating with a thickness of 250nm is intact and not broken.
[0047] Figure 2 The surface potential difference and surface morphology of the material modified by the tantalum coating prepared in Comparative Example 1 of the present invention are shown. As can be seen from the figure, the potential difference of the tantalum coating with a thickness of 250 nm is 160 mV, and the surface is relatively smooth.
[0048] Figure 3 This is a microscopic morphology of the material fault of the tantalum coating modified by comparative example 2 of the present invention. It can be seen from the figure that the tantalum coating with a thickness of 500 nm is intact and not broken.
[0049] Figure 4 The surface potential difference and surface morphology of the material modified by the tantalum coating prepared in Comparative Example 2 of the present invention are shown in the figure. As can be seen from the figure, the potential difference of the tantalum coating with a thickness of 500nm is 210mV, and the surface is obviously rougher.
[0050] Figure 5 This is a microscopic morphology of the material fault of the tantalum coating modified by comparative example 3 of the present invention. It can be seen from the figure that the tantalum coating with a thickness of 750nm is intact and not broken.
[0051] Figure 6 The surface potential difference and surface morphology of the material modified by the tantalum coating prepared in Comparative Example 4 of the present invention are shown. It can be seen from the figure that the potential difference of the tantalum coating with a thickness of 500nm is 170mV, and the surface roughness is also higher than that of the tantalum coating with a thickness of 250nm.
[0052] Figure 7 This is a fault microscopic morphology of the material modified with the tantalum-silver coating obtained in Example 1 of the present invention. As can be seen from the figure, the tantalum-silver coating is intact and not broken.
[0053] Figure 8 The surface potential difference and surface morphology of the material modified by the tantalum-silver coating prepared in Example 1 of the present invention are shown. It can be seen from the figure that the surface potential difference of the tantalum-silver coating is 380 mV. The high potential difference can affect the cell membrane potential and form an endogenous electric field, thereby promoting bone integration. The surface roughness is also significantly higher than that of the simple tantalum coating.
[0054] Example 2 A method for preparing a tantalum-silver coating-modified bone implant comprises the following steps: S1: Pre-treating the substrate, wherein the substrate is placed in acetone, alcohol and deionized water for ultrasonic cleaning in sequence, and then vacuum dried at 150°C, wherein the vacuum degree is 10 -2 Pa; S2: In an argon atmosphere with a purity of more than 99.999% and a flow rate of 20 sccm, tantalum and silver are sequentially deposited on the surface of the pretreated base metal by a magnetron sputtering method, and the magnetron sputtered substrate is heat-treated at 150° C. for 3 hours to obtain the tantalum-coated modified bone implant.
[0055] During the magnetron sputtering process, the target current was 1A, the magnetron sputtering time was 18 min, and the vacuum degree was 10 -5 Pa, in addition, during the magnetron sputtering process, a negative bias voltage is applied between the target and the substrate, and the bias voltage is -200 V. At the same time, during the magnetron sputtering process, a magnetic field is applied between the target and the substrate, and the magnetic field strength is 200G.
[0056] The thickness of the tantalum-silver coating is 200 nm.
[0057] Example 3 A method for preparing a tantalum-silver coating-modified bone implant comprises the following steps: S1: Pre-treating the substrate, wherein the substrate is placed in acetone, alcohol and deionized water for ultrasonic cleaning in sequence, and then vacuum dried at 300°C, wherein the vacuum degree is 10 -3 Pa; S2: In an argon atmosphere with a purity of greater than 99.999% and a flow rate of 100 sccm, tantalum and silver are sequentially deposited on the surface of the pretreated base metal by a magnetron sputtering method, and the magnetron sputtered substrate is heat-treated at 150° C. for 3 hours to obtain the tantalum-coated modified bone implant.
[0058] During the magnetron sputtering process, the target current was 3A, the magnetron sputtering time was 450min, and the vacuum degree was 10 -3 Pa, in addition, during the magnetron sputtering process, a negative bias voltage is applied between the target and the substrate, and the bias voltage is -150 V. At the same time, during the magnetron sputtering process, a magnetic field is applied between the target and the substrate, and the magnetic field strength is 500G.
[0059] The thickness of the tantalum-silver coating is 5 μm.
[0060] Example 4 A method for preparing a tantalum-silver coating-modified bone implant comprises the following steps: S1: Pre-treating the substrate, wherein the substrate is placed in acetone, alcohol and deionized water for ultrasonic cleaning in sequence, and then vacuum dried at 200°C, wherein the vacuum degree is 10 -3 Pa; S2: In an argon atmosphere with a purity of more than 99.999% and a flow rate of 50 sccm, tantalum and silver are sequentially deposited on the surface of the pretreated base metal by a magnetron sputtering method, and the magnetron sputtered substrate is heat-treated at 300° C. for 2 hours to obtain the tantalum-coated modified bone implant.
[0061] During the magnetron sputtering process, the target current was 2A, the magnetron sputtering time was 90 min, and the vacuum degree was 10 -4 Pa, in addition, during the magnetron sputtering process, a negative bias voltage is applied between the target and the substrate, and the bias voltage is -100 V. At the same time, during the magnetron sputtering process, a magnetic field is applied between the target and the substrate, and the magnetic field strength is 300G.
[0062] The thickness of the tantalum-silver coating is 1 µm.
[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a tantalum-silver coating modified bone implant, characterized in that: The method comprises depositing tantalum and silver on the surface of a base metal in sequence by a magnetron sputtering method under an argon atmosphere, and heat-treating the base material after magnetron sputtering to obtain the tantalum coating modified bone implant.
2. The method for preparing a tantalum-silver coating modified bone implant according to claim 1, characterized in that: The purity of the argon gas is greater than 99.999%, and the flow rate of the argon gas is 20-100 sccm.
3. The method for preparing a tantalum-silver coating modified bone implant according to claim 1, characterized in that: During the magnetron sputtering process, the target current is 1-3A, and the magnetron sputtering time is 18-450min.
4. The method for preparing a tantalum-silver coating modified bone implant according to claim 1, characterized in that: During magnetron sputtering, the vacuum degree is 10 -3 ~10 -5 Pa.
5. The method for preparing a tantalum-silver coating modified bone implant according to claim 1, characterized in that: During magnetron sputtering, a negative bias voltage of -100~-200V is applied between the target and the substrate.
6. The method for preparing a tantalum-silver coating modified bone implant according to claim 1, characterized in that: During magnetron sputtering, a magnetic field with a strength of 200~500G is applied between the target and the substrate.
7. The method for preparing a tantalum-silver coating modified bone implant according to claim 1, characterized in that: The heat treatment temperature is 150-300° C. and the time is 1-3 hours.
8. The method for preparing a tantalum-silver coating modified bone implant according to claim 1, characterized in that: Before magnetron sputtering, the substrate was pretreated by placing the substrate in acetone, alcohol and deionized water for ultrasonic cleaning, and then vacuum drying at 150-200°C, wherein the vacuum degree was 10 -3 ~ 10 -2 Pa.
9. A tantalum-silver coating modified bone implant, characterized in that: The tantalum coating is prepared by the method described in any one of claims 1 to 8; the bonding strength between the tantalum coating and the bone implant is 20 to 60 MPa, and the roughness is 15 to 100 nm.
10. The tantalum-silver coating modified bone implant according to claim 9, characterized in that: The thickness of the tantalum coating is 200nm~5µm.
Citation Information
Patent Citations
Anti-infection titanium tantalum bone implantation object and preparing method thereof
CN104905893A
Tantalum-silver coating dental implant and preparation method thereof
CN114164366A
Orthopedic implant plated with tantalum plating layer on surface and preparation method thereof
CN116334542A
Multilayer-structure tantalum-silver film implanted into surface of medical device and preparation method of multilayer-structure tantalum-silver film
CN116688229A
The formation method of porous antibacterial coatings on titanium and titanium alloys surface
EP3816327A1